Students' social origins, educational process and post-college outcomes: The case of an elite Chinese university. (January 2020) - Niu, Sunny Xinchun; Zheng, Yajun; Yang, Fei
Scholars debate whether and how higher education and elite education experiences break or reinforce the link between social origins and status attainment in meritocratic societies. We contribute to these debates focusing on post-college outcomes of elite university students in contemporary China. Using a longitudinal survey of the 2014 freshmen cohort from an elite Chinese university and a sequential logit modeling technique, we find that meritocracy is seemingly at play between the trajectories of graduate study and employment. However, within each trajectory, students' hukou (urban/rural registration status) and regional backgrounds significantly constrain their post-college options, partly through differential participation in high-impact educational practices. Furthermore, social origins leave marks on students' motives for graduate study.